Partial dosages of Caesalpinia Spinosa ash and cement fiber in asphalt mixtures for flexible pavements (Gaceta Técnica, 2025)
This experimental study evaluates the influence of the partial addition of Caesalpinia Spinosa ash (CS) or Tara ash, and Fiber Cement (FC) in asphalt mixtures for flexible pavements. Mineral filler replacement percentages of 1,0%, 1.5% and 2,5% were analyzed using the Marshall and Lottman tests, with the aim of determining their effect on stability, creep and resistance to moisture. This mixture improves its properties, therefore. tend to be applicable to roads. A total of 51 briquettes of selected asphalt mixture were manufactured. The distribution of specimens was organized into two groups: the first composed of 27 specimens for the Marshall test and the second by 24 for the Lottman test. From the pattern set (0% modification), 18 briquettes were prepared for the Marshall test, and 6 were intended for the and Lottman tests. In the case of the mixtures modified with additives at concentrations of 1,0%, 1,5% and 2,5%, 3 and 6 specimens were prepared for each test, respectively. The results of the Marshall test indicate a decrease in stability compared to the standard sample (1289,9 kg), with values of 1271,9 kg, 1198 kg, and 1256 kg for 1.0%, 1,5%, and 2,5% CS+FC, respectively. Creep values ranged from 2,91 mm for the standard sample to 3.5 mm, 3.26 mm, 3.08 mm, and 2,93 mm, depending on the addition percentage. Finally, the indirect tensile strength test (TSR) showed values of 82,7%, 79,6%, 81,2%, and 76,7%.
Keywords: Caesalpinia Spinosa ash; cement fibers; modified asphalt mixtures